A NEW MONOTERPENE SYNTHASE GENE INVOLVED IN THE MONOTERPENE PRODUCTION FROM LILIUM 'SIBERIA' - Z. H. Hu; T. J. Li; J. Zheng; P. S. Leng; 3; K. Yang; K. Z. Zhang (Journal of Animal and Plant Sciences, 2016)
Floral scent is thought to be an important characteristic to evaluate ornamental flowers, playing a key role in plant ecophysiology. Monoterpenes are an important category of floral scent compounds. In this study, the monoterpene emission from the Lilium 'siberia' flowers was investigated using the automated thermal desorption-gas chromatography/mass spectrometry (ATD-GC/MS) technique. It was found that monoterpenes were the dominant components of floral scent, and showed a significantly developmental emission. The release amounts of monoterpenes first increased and then decreased during the developmental stages, peaking at the full opening stage. In the following study, the first monoterpene gene in Lilium, named Li-mTPS, was cloned. Due to the presence of conserved DDxxD motif and RRx8W motif, the deduced Li-mTPS was classified into TPS-b monoterpene synthase subfamily. The tissue-specific expression of Li-mTPS revealed the highest level in the outer petals. Li-mTPS expression showed similar pattern with monoterpene emission except that the peaking time was earlier than monoterpene emission. It was concluded that the Li-mTPS expression played a key role in monoterpene emission from Lilium 'siberia' flowers. But other regulatory mechanisms also may contribute to the production and emission, which needs to be investigated in the future study.
Keywords: Floral scent; Lilium 'siberia'; Monoterpene emission; Monoterpene synthase gene